Role of gender in health disparity: the South Asian context - Fikree, Fariyal F (BMJ Publishing Group Ltd., 2004)
South Asia's girls and women do not have the same life advantage as their Western counterparts. A human rights based approach may help to overcome gender related barriers and improve the wellbeing of men, women, and children.